The influence of fire on soil properties under slash-and-burn agriculture management in a hillside environment in the Atlantic Forest biome - Bertolino, Ana Valéria Freire Allemão; Mattos, Bruno Souza; Bertolino, Luiz Carlos (Sociedade & Natureza, 2022)
The objective of this study was to evaluate the effect of fire on the transformation of the soil’s physical (granulometry and porosity), chemical (organic matter and pH) and mineralogical properties in an area where slash-and-burn farming predominates. The study was conducted in the district of São Pedro da Serra, municipality of Nova Friburgo, Rio de Janeiro state, Brazil, with relief formed by steep slopes interspersed with valleys. The region has a Tropical Altitude Climate, characterized by hot, rainy summers and mild, dry winters. The average annual rainfall is 1.279 mm, with the wettest months from November to March, and the driest months from May to August, marking the seasonal rainy (summer) and dry (winter) period.. We collected deformed and undeformed soil samples at three depths (0-5 cm, 5-10 cm and 10-15 cm), in two areas, one that had been subject to high-intensity fire (HIF) and the other where traditional slash-and-burn agriculture is practiced (S&B), with low-intensity fire. The physical, chemical and mineralogical properties of the soil had distinct responses to the disruption caused by fire of varying intensity. In the HIF area, the soil was hydrophobic, accompanied by smaller pore size (microporosity). In the S&B area, in contrast, the soil had a greater percentage of macropores. The results suggest that slash-and-burn agriculture, where there are fallow intervals, less severely affects the soil properties.